Linguistic Variations and Social Functions of Slang in Indonesian Television Talk Shows: A Sociolinguistic Study of Brownis Trans TV - Dina Apriyanti; Ixsir Eliya (JPI: Jurnal Pustaka Indonesia, 2023)
This study investigates the forms, meanings, and social functions of slang expressions in the Indonesian television talk show Brownis on Trans TV, a program widely recognized for its humorous and informal interactions. Slang, as a dynamic variety of language, plays a central role in shaping youth identity and media discourse, yet its use in mainstream entertainment contexts remains underexplored. Employing a qualitative descriptive design with a content analysis approach, twenty episodes broadcast between May and June 2022 were purposively selected and transcribed. Data collection involved systematic observation and documentation, while the analytic procedure consisted of identifying slang items, classifying them into forms, interpreting their semantic dimensions, and analyzing their communicative functions. The findings revealed four primary forms of slang basic words, reduplications, abbreviations, and phrases with abbreviations and basic words being the most frequent. Semantically, slang operated at lexical, grammatical, terminological, and reflective levels, while functionally it facilitated social bonding, attracted attention, delivered satire, compressed expressions, enriched vocabulary, created intimacy, and generated humor. Frequency analysis showed that a few dominant terms such as gue, elo, and bucin coexisted with a wide range of less frequent but innovative expressions, as visualized through bar charts and word clouds. These outcomes suggest that televised discourse not only mirrors youth linguistic practices but also amplifies and legitimizes them, contributing to the diffusion of non-standard language in Indonesian society. The study contributes a novel perspective to sociolinguistic research by situating slang within entertainment media, with implications for cultural studies, language education, and media literacy, while also noting limitations in scope and duration that future research should address.